2012
DOI: 10.1016/j.crohns.2011.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency in Crohn's disease: Prevalence, risk factors and supplement use in an outpatient setting

Abstract: Vitamin D deficiency was common in patients with CD and associated with longstanding disease, smoking and winter. While over 40% of patients used a vitamin D-containing supplement, the dosages were inadequate to prevent deficiency. Appropriate vitamin D screening and supplementation should be considered in the context of health promotion of outpatients with CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
75
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(90 citation statements)
references
References 36 publications
12
75
1
2
Order By: Relevance
“…This is a factor known to be associated with a more severe course of illness. Our data agree with what has been already reported in the literature by several authors [20,[25][26][27]. The mechanism linking the two aspects has not been clarified yet.…”
Section: International Journal Of Digestive Diseasessupporting
confidence: 81%
See 3 more Smart Citations
“…This is a factor known to be associated with a more severe course of illness. Our data agree with what has been already reported in the literature by several authors [20,[25][26][27]. The mechanism linking the two aspects has not been clarified yet.…”
Section: International Journal Of Digestive Diseasessupporting
confidence: 81%
“…The role of the corticosteroid therapy in patients with IBD has been generally limited to the evaluation of the relationship with alterations in bone densitometry. Few case studies have considered the relationship with the serum level of 25-OH-vitamin D, and in general these studies tend to exclude an inverse correlation between the corticosteroid therapy and the reduction of circulating levels of vitamin D [20]. In our study we revealed a positive correlation between the history of steroid-dependence and reduced levels of vitamin D, while there would be no correlation with the use of corticosteroids under 25 years of age.…”
Section: International Journal Of Digestive Diseasescontrasting
confidence: 32%
See 2 more Smart Citations
“…Prevalence of deficiency may range from 35 to 100% in CD (21) , when deficiency is defined as circulating 25-hydroxyvitamin D (25(OH)D) <50 nmol/l (22) and applied across a range of published studies. The exact cause of IBD remains unknown; however, the disease is thought to result from a complex interaction between immunological, genetic and environmental factors.…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%